A novel immunomodulatory hemocyanin from the limpet Fissurella latimarginata exhibits outstanding anti-tumor activity in melanoma. - LAVELLE, EDWARD (My University, 2014)
Hemocyanins, the huge oxygen-transporting glycoproteins of some mollusks, are used as immunomodulatory proteins with proven anti-cancer properties. The biodiversity of hemocyanins has promoted interest in identifying new anti-cancer candidates with improved immunological properties. Hemocyanins promote Th1 responses without known side effects, which make them ideal for long-term sustained treatment of cancer. In this study, we evaluated a novel hemocyanin from the limpet/gastropod Fissurella latimarginata (FLH). This protein has the typical hollow, cylindrical structure of other known hemocyanins, such as the keyhole limpet hemocyanin (KLH) and the Concholepas hemocyanin (CCH). FLH, like the KLH isoforms, is composed of a single type of polypeptide with exposed N- and O-linked oligosaccharides. However, its immunogenicity was significantly greater than that of KLH and CCH, as FLH induced a stronger humoral immune response and had more potent anti-tumor activity, delaying tumor growth and increasing the survival of mice challenged with B16F10 melanoma cells, in prophylactic and therapeutic settings. Additionally, FLH-treated mice demonstrated increased IFN-γ production and higher numbers of tumor-infiltrating CD4(+) lymphocytes. Furthermore, in vitro assays demonstrated that FLH, but not CCH or KLH, stimulated the rapid production of pro-inflammatory cytokines (IL-6, IL-12, IL-23 and TNF-α) by dendritic cells, triggering a pro-inflammatory milieu that may explain its enhanced immunological activity. Moreover, this effect was abolished when deglycosylated FLH was used, suggesting that carbohydrates play a crucial role in the innate immune recognition of this protein. Altogether, our data demonstrate that FLH possesses increased anti-tumor activity in part because it activates a more potent innate immune response in comparison to other known hemocyanins. In conclusion, FLH is a potential new marine adjuvant for immunization and possible cancer immunotherapy.
PUBLISHED
Keywords: Melanomas; Melanoma cells; Immune response; Enzyme-linked immunoassays; Cytokines; Antigens; Antibodies; Cancer; Immunology, Inflammation & Infection